The Cambridge handbook of personality psychology - Corr, Philip J.; Matthews, Gerald (Cambridge University Press, 2020)
Personality psychology is a rapidly maturing science making important advances on both conceptual and methodological fronts. The Cambridge Handbook of Personality Psychology offers a one-stop source for the most up-to-date scientific personality psychology. It provides a summary of cutting-edge personality research in all its forms, from DNA to political influences on its development, expression, pathology and applications. The chapters are informative, lively, stimulating and, sometimes, controversial and the team of international authors, led by two esteemed editors, ensures a truly wide range of theoretical perspectives. Each research area is discussed in terms of scientific foundations, main theories and findings, and future directions for research. With useful descriptions of technological approaches (for example, molecular genetics and functional neuroimaging) the Handbook is an invaluable aid to understanding the central role played by personality in psychology and will appeal to students of occupational, health, clinical, cognitive and forensic psychology